Estuarine and coastal connectivity of an estuarine-dependent fishery species, Pomadasys commersonnii (Haemulidae). Issue 1 (2nd January 2017) - Dames, MH; Cowley, PD; Childs, A-R; Bennett, RH; Thorstad, EB; Næsje, TF
Abstract : Understanding the level of connectivity between estuarine and coastal waters is essential for appropriate management of estuarine-associated taxa. Most studies have focused on the role of a single estuary, while limited research exists on the importance of multiple estuaries to individuals of estuarine-associated species. This study used acoustic telemetry to assess the usage of multiple estuaries and coastal waters by the estuarine-dependent spotted grunter Pomadasys commersonnii . Twenty-six adult fish were tagged with acoustic transmitters in the Kariega and Bushmans estuaries, South Africa, and their movements along a 300-km stretch of Indian Ocean coastline were monitored for up to 17 months. Tagged individuals spent most of their time in the estuary where they were tagged (55% and 85% for fish tagged in the two estuaries, respectively), followed by time in the sea (30% and 15%) and in other estuaries (15% and <1%). The mean durations of sea trips for fish tagged in the Kariega Estuary or Bushmans Estuary, respectively, were 25 days (range 3–55) and 12 days (range 2–22). Of the fish that went to sea, 93% from the Kariega Estuary and 60% from the Bushmans Estuary visited other estuaries. Most visits were undertaken to the Swartkops, Bushmans and Kowie estuaries, although the longest durations were spent in the Sundays Estuary. Individuals moved to estuaries up to 130 km away. The total distance travelled between estuaries by an individual during the study was ∼529 km, with means of 201 and 184 km, respectively, for fish tagged in the Kariega and Bushmans estuaries. Despite covering large distances between estuaries, individuals often returned to their tagging estuary. Residency in their tagging estuary, combined with frequent visits to a neighbouring estuary, highlights the importance of estuarine habitats for this popular fish species, even after reaching maturity.